Soviet Household Saving Behavior - Pickersgill, Joyce (The Review of Economics and Statistics, 1976)
A LTHOUGH there are many differences I between planned and market economies, both with respect to the locus of decisionmaking power and the institutions designed to allocate resoturces, household behavior in the two economies may be quite similar. Both Soviet and Western households determine the allocation of their time between work and leisure in response to their preferences and the real wage. Although the Soviet worker does have a limited ability to choose the number of hours he works in his primary place of employment, he can choose to increase or decrease his work effort in response to bonus schemes. He may also get a second job or allocate some time to quasi-legal, free-market activities. Once this choice is made, each household has a certain money income that it may devote to present consumption or save for future consumption. Making the assumption that Soviet households, like their Western counterparts, wish to maximize the utility derived from consumption over their lifetime, we may observe them transferring income from the present to the future, or in the reverse direction, depending upon their present and expected future money income, the current and expected future price of commodities, the interest rate, and their rate of time preference, restricted, of course, by the limited availability of consumer credit. Although the motives for saving may be similar for Soviet and Western households, the significance of saving behavior in the two contexts is quite different. A main concern of those investigating saving behavior in developed market economies has been the relationship between aggregate demand and the level of output and employment. The investigation of saving behavior in developing market economies focuses on the need for increased savings in the household sector to finance ambitious investment programs.1 In the Soviet Union the significance of household saving behavior is different from the two cases above. The resources for the planned level of investment are determined by the central planners independently of household saving decisions, and the remainder of the resources, after subtracting such items as defense and the costs of government administration, are made available for the production of public and private consumer goods. A sales tax on consumer goods is set by the planners to equate the supply of, and demand for, these goods. Thus, in theory the saving decisions of Soviet households do not influence either the total level of output or the share of output devoted to consumption and investment. The above analysis of the Soviet economy, however, is an oversimplification and ignores the impact that Soviet household saving behavior can have on the outcome of the plan. If households are saving at their desired rate, but this rate is greater than anticipated by the planners, a part of the planned output of consumer goods will not be sold and unplanned increases in inventories will result, given that prices are not responsive to excess supply. Assuming the planned level of inventories is considered optimal, these unplanned inventory increases represent a waste of resources, and when they occur they are, and ought to be, of considerable concern to Soviet planners. On the other hand, if money wages are rising rapidly and households find that they are saving at a rate faster than desired, they will attempt to buy more goods and services with the excess savings. To the extent that prices and the supply of consumer goods are completely determined by the planners, and both are unresponsive to consumer demand, households will be unsuccessful in their attempt to purchase goods and to reduce their saving rate, and may choose to reduce their work effort instead. In fact, Soviet planners do not completely determine the price and supply of consumer Received for publication September 30, 1974. Revision accepted for publication June 9, 1975. 1 There is a substantial literature on the effect of rising incomes on savings in developing economies. For a survey of this literature see Mikesell and Zinser (1973).